10-7=-6(z+5)

Simple and best practice solution for 10-7=-6(z+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-7=-6(z+5) equation:


Simplifying
10 + -7 = -6(z + 5)

Combine like terms: 10 + -7 = 3
3 = -6(z + 5)

Reorder the terms:
3 = -6(5 + z)
3 = (5 * -6 + z * -6)
3 = (-30 + -6z)

Solving
3 = -30 + -6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '6z' to each side of the equation.
3 + 6z = -30 + -6z + 6z

Combine like terms: -6z + 6z = 0
3 + 6z = -30 + 0
3 + 6z = -30

Add '-3' to each side of the equation.
3 + -3 + 6z = -30 + -3

Combine like terms: 3 + -3 = 0
0 + 6z = -30 + -3
6z = -30 + -3

Combine like terms: -30 + -3 = -33
6z = -33

Divide each side by '6'.
z = -5.5

Simplifying
z = -5.5

See similar equations:

| 651=129+58m | | 6*(-3)+7y=4*(-3)+4y | | K-2=2+3k | | -2n-10=8 | | -4(-8+3k)-3k=122 | | d+126=98 | | 6-6x=5x-9x--2 | | 12.51-0.08h=13.01-0.13h | | b+24=36 | | 10(x-4)+4x=14x+21 | | 5y-4(3y+11)=12 | | (6x^3)(8x)= | | (a-9)(a-4)= | | r-12=42 | | x^2-2x=5x+18 | | r+10=66 | | -13+4k=k+8 | | 8(n+3)=-14-5(n-5) | | 25=5+3k | | t-58=71 | | 4x+2(4x-12)=108 | | 14+1x+1x+9=11 | | -2(1)=x | | 18-.4(16)=x | | -215w-71+9=-7 | | 3k4-28-2k3=37 | | (1/4)=9n | | 4n+9=16n-1 | | 16c=5-7 | | -3=(4+7)-15 | | 1-7k=-8k+9 | | 8(d+6)=3(d-7)+5d |

Equations solver categories